Efeito da fragmentação de um rio do semiárido na estrutura da assembleia de peixes e na alimentação de peixes detritívoros - Oliveira, Jean Carlos Dantas de (2020)
The regulation of river systems through the arrangement of cascading reservoirs along the main river causes marked changes in the composition of fish communities, as in the patterns of water flow, altering the transport of water, debris, sediments and nutrients along the cascades of reservoirs. Thus, the objective of the study was to evaluate the richness and abundance of fish assemblages in the reservoir cascade system on the Apodi / Mossoró river on the Brazilian semiarid region, as well as to analyze the diet of Prochilodus brevis and Curimatella lepidura that present detritivorous/iliófagas eating habits between the reservoirs. The Apodi / Mossoró basin is located in the eastern Northeast of Brazil, occupying an area of 14,276 km2, with an intermittent hydrographic network and with a heavily altered flow due to the construction of reservoirs, which are currently 618. In the main channel of the river, the reservoirs of Major Sales, Angicos, Flechas, Pau dos Ferros and Santa Cruz are cascaded. The sampling occurred quarterly, during the months of February, May, August and November, in the period of 2011 to 2012 in the Pau dos Ferros reservoir, and in 2015 and 2016 to the other reservoirs. The individuals were captured with eleven gillnets with meshes varying between 12, 15, 20, 25, 30, 35, 40, 45, 50, 60 and 70 mm (between adjacent knots), with 15m in length and height of 2, 0m per collection sites, exposed parallel to the margins for a period of 12 hours. The trials and identification of the specimens took place according to specialized literature, being later confirmed and / or corrected by a taxonomist at the Federal University of Paraíba (UFPB). In order to determine whether the richness and abundance of native non-migratory, native migratory and non-native fish assemblages differ between reservoirs along the cascade, Kruskal-Wallis non-parametric analysis of variance was applied, followed by Wilcoxon test between groups, for richness and CPUEn separately. Analysis of the detritivorous species' diet was done through the alimentary importance index (IAI%). The Apodi/Mossoró River reservoir cascade, associated with the peculiar characteristics of the intermittent regime river systems, are adverse environments that did not favor migratory species habit, especially in the cascade upstream reservoirs, endangering some species, which presented low abundance values, to disappearing on local scales. The findings of the predominance of debris, sediment and plant material in the diet of the two species, but with different contributions in the reservoirs along the cascade, indicate that the species have a narrow trophic niche, possibly consuming the most abundant food resources in the environment that allows the coexistence of the two species, even with diet overlap